Students' perceptions on medical education at Marmara University School of Medicine - (:unkn) unknown (My University, 2000)
Objective: The aim of this descriptive study was to evaluate the students' perceptions relating to medical education at Marmara University School of Medicine in order to include their opinions and recommendations in future curricular and methodological changes in medical education. Methods: Data was collected by a questionnaire. Eighty four recent graduates participated in the study; the response rate was 60.4%. Results: The graduates were pleased to be asked their opinions. The majority agreed that there was need for a 'moderate change' in the educational system of Marmara University School of Medicine. Graduates who reported 'changes in the educational system are necessary' indicated that necessary changes should be done basically in areas such as educational methods, curriculum, audio-visual materials, training skills and assessment/evaluation methods. Conclusion: This 'baseline evaluation' is considered as the initial step towards the improvement process of medical education in Marmara University School of Medicine, since the necessary changes were highlighted by the results. These results demonstrated conformity between the opinions and expectations of students, and the needs, principles and suggestions stated by the Institutional Undergraduate Education Investigation, Planning and Coordination Committee. The initial research provided a hopeful perspective in openness to and compliance with the change process at Marmara University School of Medicine.
Keywords: Changes in medical education; Medical education; Students' perceptions